Pengaruh Sukuk Korporasi dan Total Aset Perbankan Syariah Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2016-2020 - Muhammad Ikhsan Harahap; Imsar Imsar; Rahmah Nur Dongoran (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the effect of corporate sukuk and total assets of Islamic banking on economic growth in Indonesia. This study uses two independent variables of corporate sukuk and total assets of Islamic banking with one dependent variable, namely economic growth. In this study, the population is data from the Financial Services Authority (OJK) and the Central Statistics Agency (BPS) regarding data on corporate sukuk, total Islamic banking assets and national economic growth for the last eight years, namely data from 2016 to 2020 with using data interpolation as much as 60 data and using a saturated sample technique, namely all data from 2016 - 2020. The data analysis method used is quantitative analysis with secondary data. The results of his research partially corporate sukuk have a positive and significant effect on economic growth. Partially, the total assets of Islamic banking have a negative and significant effect on economic growth. The value of t table is 1.67203. when compared with t count 8.086248 > from t table 1.67203, it can be said that corporate sukuk variables have an effect on economic growth. Then the variable total assets of Islamic banking has a t count of 10.22120 > from t table 1.67203, meaning that the variable total assets of Islamic banking has an effect on economic growth. Simultaneously (equally) the independent variables of corporate sukuk and total assets of Islamic banking have a significant and significant effect on economic growth with a probability value of 0.0000